TRANSPORT INNOVATIONS AS A FACTOR AFFECTING THE MODERNIZATION OF TRANSPORT TECHNOLOGY BACHELOR’S TRAINING AT UKRAINIAN UNIVERSITIES - Лебідь, Ірина Георгіївна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article concentrates on the analysis of modern innovations and development trends in the transport system from the global perspective. It looks at the main consequences the introduction of such technological advancements will have for society as a whole emphasizing the required changes in the transportation industry and transport technology professionals` knowledge and skills. The paper aims to draw a parallel between the innovative development tendencies in transport technologies and the state of professional training of bachelors majoring in specialty 275 “Transport technology” at Ukrainian universities. The study is based on the following methods: structural and system analysis, systematization, comparison and synthesis of information sources, experience, and achievements in this field, as well as pedagogical design for modeling the possibilities of applying the obtained results in the national educational practice. The article highlights the main transport technology development trends (computerization as well as the development and implementation of technological solutions that make transport more environmentally friendly, energy-efficient and cost-effective, stepping up the requirements for industry employees` professional training); the state of transport technology bachelors` training at the institutions of higher education in Ukraine is identified as satisfactory; it is carried out in the direction of knowledge formation and development of skills mostly in traditional transport-related disciplines. However, the training content should be complemented by courses in information technology and innovative transport systems and processes